Perancangan Digital Photobook Sebagai Media Pendukung Marketing Produk Tinctori - Vincentius Satria Wiratama; Martin Setyawan; Birmanti Setia Utami (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Tinctori is a company focused on sustainable fashion products using natural dyes. Based on observations and interviews, Tinctori’s existing promotional media are still limited and have not effectively conveyed its sustainability values or modern fashion appeal. Therefore, a more engaging, informative, and accessible promotional medium is needed. This study aims to design a digital photobook as a marketing support medium for Tinctori’s products. The research uses a qualitative method with a linear strategy, consisting of problem identification, data collection, analysis, design, and testing stages. The result is an interactive e-book–based digital photobook that presents the company profile, production process, and product catalog of Tinctori. Based on the testing results, the media was considered attractive, communicative, and effective in conveying the brand message and increasing audience interest. This research is expected to serve as an example of efficient, eco-friendly digital media that supports sustainable fashion promotion in Indonesia.